Adverse events related health care in Brazil: An ecologic study between 2014-2018 (Research, Society and Development, 2021)
Objectives: To identify the types of incidents most notified to the National Health Surveillance Agency through the computerized system, since the implementation of patient safety centers in the country. Method: Ecological study based on the data obtained from the Patient Safety and Quality in Health Services Information Bulletins related to health care issued by ANVISA and the National Registry of Health Facilities (CNES) from 2014 to 2018. Results: The data were subjected to the Kolmogorov-smirnovi normality test, and a non-parametric approach was chosen (Sperman, Wilcox, Kruskal-Wallis) with a significance level of 5%. The results showed that both in the biennia 2015-2016 and 2017-2018 the most prevalent types of incidents were: failure during assistance (27.8% /22.2%); pressure injury (17% / 18.6%); fall (11.1% / 11%); failure to identify the patient (6.3% / 8%); loss or obstruction of tube (7.5% / 6.5%) and phlebitis (5.4% / 4.9%). Conclusion: Despite the advances achieved, much remains to be done to establish safety culture in health institutions and to report these adverse events.